Linguistic-Etymological Classification of The Bukhara District - Adizova Nodira Bakhtiyorovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The linguistic-etymological classification of Bukhara district toponymy is presented in this article. The names of some microtoponms include the names of the Turkic peoples, including the tribes and tribes of the Uzbek people, and their branches and networks, and we have analyzed and commented on them